Analysis of road networks (The landscape approach and Spatial syntax), Case of the Biskra road (Batna - Algeria) - Khireddine, Dounia; Aichour, Boudjemâa (Technium Social Sciences Journal, 2022)
The urban landscape is a concept closely linked to the comfort and well -being of the citizen. Today, producing a remarkable urban landscape has become an important issue in all countries of the world, a correct image that emerges from a product built frame is considered a capital gain for the attractiveness of the territory. This work is essentially interested in the urban landscape as a perceived quality, and according to a sensitive method combined with a visibility study with the tools of spatial syntax, applied to the case of study namely the city of Batna in Algeria, the 'Study of a historic street in the city, shows which urban landscape is in perpetual transformation. Recent changes have negatively influenced the image of the city's urban landscape and it is necessary to take urban measures in order to preserve it.